Strategic Analysis of The Fire and Rescue Service Preparation of Medan City in Handling Disaster Incidents Fire in 2023 - Mutiara, Grace; Ketaren, Otniel; Damanik, Elsarika; Manurung, Kesaktian; Sinaga, Janno (Griya Eka Sejahtera, 2025)
Background: Fire is one of the disasters that has a significant impact on safety and property. Medan City, as a centre of urban activities with a high population density, faces a significant risk of fire. Therefore, the readiness of the Medan City Fire and Rescue Department is a crucial factor in fire countermeasures. This research aims to analyse the readiness strategies of the agency in dealing with fires.Methods: This study was conducted in Medan City using a descriptive qualitative approach. The informants included the head of the service, heads of various fields, and operational fire extinguisher officers. Data collection techniques comprised in-depth interviews, observations, and document studies. Data analysis employed the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion extraction.Results: The research findings indicate that the Medan City Fire and Rescue Department's readiness still faces several challenges, including a lack of trained personnel, limited facilities and infrastructure, and constraints in inter-agency coordination. The strategies implemented include regular training improvements, budget optimisation, and strengthening cross-sector synergy.Conclusion: The readiness of the Medan City Fire and Rescue Department in addressing fires requires strengthening in terms of human resources, logistics, and collaboration with various stakeholders. The results of this research have important implications for the development of disaster mitigation policies in the field of public health and safety.